CYP3A5 POLYMORPHISM AND THE RISK OF CANCER: A METAANALYSIS - Khan, Muhammad Tahir; Sahar (European Scientific Journal, ESJ, 2014)
The two important genes of CYP450 are CYP3A4 and CYP3A5 that play a central role in drugs and hormones metabolisms that have a role in the etiology of cancers. Single nucleotide polymorphism (SNP) in these genes may increase the risk of developing cancers. Numerous functional SNPs of the CYP3A5 gene have been connected in cancer risk, but individually published investigation have exposed questionable consequences. The aim of the current investigation and meta-analysis was to examine the link between polymorphism CYP3A5*3 6986 A>G [rs776746] under the heterozygous model and an association with increased risk of cancer. Following the inclusion criteria, eight studies were incorporated and 42 studies were excluded in this metaanalysis. The numbers of cancer cases and healthy controls were 4959 and 5176, respectively. The heterogenecity model was significant in subgroup analysis of Chinese, Indian, Japanese and Asian population suffered in TB, CML, and breast cancers [OR: 0.50, 95 %CI: 0.30-0.81, P<0.01; OR= 1.57, 95 %CI: 1.00-2.47, P<0.05; OR=0.69; 95%CI=0.51-0.93; P<0.01; OR=0.61; 95%CI=0.42-0.89; P<0.01]. The overall statistics under heterozygous model [Fig: 2; OR=0.9187; 95%CI=0.82-1.02; P<0.1289] showed that polymorphism, CYP3A5*3 6986 A>G [rs776746] is not associated with cancer risk.